Flocculation Settling Characteristics of Ultra-Fine Iron Tailings with Rich Gypsum - Daiqiang Deng; Guodong Cao (Advances in Civil Engineering)
Because of the uniqueness of geological mineralization, tailings obtained from Chenchao Iron Mine have low SiO2 content of only 27.80%. Content of Al2O3 and MgO is 13.31% and CaSO4 is 22.09%. The fineness modulus of the ores is large enough for convenient mineral separation, thus resulting in 16.03% −5 μm particles and 27.76% −10 μm particles in the tailings, respectively. The average particle size is only 69.36 μm; it belongs to the category of very fine tailings. The natural sedimentation of tailings is extremely slow due to the comprehensive effects of their physical and chemical properties. Hence, sedimentation tests using four types of flocculating agents are conducted to accelerate the sedimentation of the tailings of Chenchao Iron Mine. Compared with natural sedimentation, the flocculating sedimentation is considerably quicker. Among the four flocculants, the sedimentation of sample using the special BASF flocculant is the fastest. When the tailings of 1 ton add this flocculant of 20 g, the maximum settling concentration reaches 60.98% after 40 min and its special gravity is 1.577 g/cm3, thus it fulfills future requirements of filling technologies. As the largest iron mine in the mid-southern region of China, Chenchao Iron Mine must turn to filling mining. This study can provide technological support for goaf management and environment-friendly treatment of solid waste in the Yangtze River basin, which plays important roles in ecological protection.